Semi-analytical flash temperature model for thermoplastic polymer spur gears with consideration of linear thermo-mechanical material characteristics. Issue 4 (18th March 2019) - Černe, Borut; Duhovnik, Jože; Tavčar, Jože
Graphical abstract: Abstract: The temperature increase that occurs during running of a polymer gear pair can be divided into two components: the nominal and flash temperatures. The latter denotes the short-term temperature increase that takes place during a gear meshing cycle. A thorough analysis of the flash temperature yields an insight into the heat dissipation process, which also determines the nominal temperature increase. We focus here on the flash component using numerical and analytical computation tools, with which we can obtain realistic predictions of the temperature increase during a gear meshing cycle. The analysis is performed using a decoupled procedure that involves a mechanical finite element analysis, followed by a semi-analytical temperature evaluation method based on the computed mechanical response of the system. With it, we obtain an improved flash temperature model that offers an accurate representation of the real life thermo-mechanical processes taking place at the gear teeth contact interfaces.